The President's Daughter - Higgins, Jack (New York Berkley, 1998)
An Israeli terrorist abducts the U.S. president's illegitimate daughter--born of a liaison during the Vietnam War--and threatens to kill her if the U.S. does not attack Arab countries. The president hires a former IRA terrorist to rescue her.
Keywords: Kidnapping -- Terrorists